Validity of transcutaneous bilirubin in the first few days of life - Varughese, Pearl Mary; Kommu, Peter Prasanth Kumar; Ravichandran, K; Krishnan, Lalitha (Indian Journal of Child Health, 2017)
Objective: To study the validity of transcutaneous bilirubin (TCB) at different time points between 24 and 96 h of life. Materials and Methods: The study was conducted in a tertiary newborn center from November 2014 to June 2016. We have included all babies above 34 weeks of gestation while babies with established direct hyperbilirubinemia, neonatal septicemia, major congenital/gastrointestinal malformations and those on phototherapy were excluded from the study. After taking into consideration the inclusion and exclusion criteria, 396 babies were recruited. The correlation was analyzed using the ROC curves, and r values and plots of agreement were done using Bland Altman charts. Results: A total of 662 paired TCB and serum bilirubin readings were performed in 396 healthy neonates, at designated time points between 24 and 96 h of life. Mean TCB was found to be uniformly higher than total serum bilirubin (TSB) for all variables such as sex, birth weight, gestational age, and growth of the baby with an excellent correlation (r=0.698-0.932). The correlation between TCB and serum bilirubin improved as age increased with maximum correlation at 96 h (r=0.981). Test of agreement showed that at 24 h the TCB overestimated serum bilirubin by 1.5±0.7 mg/dl which decreased to 0.8±0.6 mg/dl by 96 h. Conclusion: TCB and TSB correlated significantly between 24 and 96 h of age. However, there is overestimation by TCB initially which decreases at 96 h.